Providing nursing care to Ebola virus disease patients: China Ebola Treatment Unit experience - Cao Jie; Zhang Lingjuan; Xi Huijun; Lu Xiaoying; Chu Danfeng; Xie Minghui; Li Li; Chen Jue (Edinburgh University Global Health Society, 2015)
Principle of "Extreme Caution" is never to be underestimated in order to reach the "Zero Infection" goal among medical and nursing staff. Ebola virus disease is not a "horrible monsters" if medical and nursing staff strictly follow personal protection principles.